External Relations of German Cities Through Intra-firm Networks—A Global Perspective - Hoyler, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
This paper adopts a global perspective to investigate external relations of German cities, both transnationally and on the national scale. At the centre of the analysis are the locational strategies of major advanced producer service firms that link the cities in which they operate through a multitude of flows. Using an interlocking network model and data on the organizational structure of leading business service firms, the paper measures and interprets the extent to which German cities were integrated in the world city network in 2008. The global positions and national network patterns of 14 major German cities are explored, as well as the sectoral strengths and geographical orientations of their external relations. The paper concludes with an assessment of the trajectory of German cities in the world city network between the turn of the twenty-first century and the onset of the current financial crisis. The analysis reveals a geography of advanced producer services that is polycentric in character but does not map directly onto the distribution of other metropolitan functions. In a longitudinal perspective, German cities experienced an absolute and relative decline in global network connectivity between 2000 and 2008, which raises questions about the changing strategic importance of German cities in the world city network.
Keywords: Advanced producer services; Cities; Connectivity; Germany; Globalization; Intra-firm networks